Effect of silver nitrate on in vitro shoot growth and tuberization in Solanum tuberosum L. - ZHANG Zhi-jun; LI Hui-zhen; HE Yun; XU Ling; ZHOU Wei-jun (浙江大学学报. 农业与生命科学版)
This study investigated the effect of AgNO3 on the in vitro shoot growth and tuberization in the closed and diffusive conditions of two potato (Solanum tuberosum L.) cultivars. After treated with AgNO3, the shoot length decreased while the root length and leaf area increased. The leaf area increased 5 and 3 fold in the closed and diffusive conditions, respectively. The water loss was significantly less in diffusive condition than in closed one, while the leaf area and shoot length increased to some extent. The application of both 7.5 and 2.5 mg·L-1 AgNO3 significantly increased the microtuber fresh weight and percentage of big microtubers for potato cultivars Dong-Nong 303 and Lanya.